DEVELOPMENT OF A SPECTROPHOTOMETRIC DETERMINATION OF PREDNISOLONE IN DIFFERENT DOSAGE FORMS - Hasan M. Luaibi; Khalid Waleed S. Al-Janabi; Ali Khalil Mahmood; Takleef Dheyab Sallal; Sumer Gaaz, Tayser (Malaysian Journal of Science, 2024)
A sensitive, accurate, and affordable colorimetric method was developed for assaying prednisolone (PRZ) in various medicinal forms. The procedure involves the oxidation of PRZ by ferric ions, followed by complexation of the resulting ferrous ions with ferricyanide to produce a greenish-blue product. Common complexation conditions were thoroughly investigated. The mole ratio of FeCl₃·6H₂O to K₃Fe(CN)₆ was 8:1. The proposed mechanism of complexation was suggested and considered. Various parameters were optimized, including the reduction of the colorimetric reaction temperature to 50°C and the duration of heating and analysis to 20-30 minutes. The calibration curve was linear over the range of 1-60 µg/mL. The limit of detection (LOD) and the limit of quantification (LOQ) were 0.5 μg/mL and 1 μg/mL, respectively. Spiking actual samples with standard PRZ showed recoveries within the 97.3-100.1% range. The method exhibited high precision, with an RSD% of less than 1.5%. Additionally, the study confirmed that common pharmaceutical excipients did not interfere. Real medicinal samples, including tablets, syrup, eye drops, and creams, were successfully examined for direct analysis of PRZ using the developed methodology, demonstrating its suitability for routine analysis of various PRZ-containing drug formulations.